Serological Diagnosis and Epidemiological impact of Helicobacter pylori infection on human health in Diyala Governorate, Iraq - Sherko Muhammed Abdulrahman; Zainab Mohammed Alzubaidy; Dhary Alewy Almashhadany; Sawsan Mohammed Sorchee (Tikrit Journal of Pure Science, 2023)
Helicobacter pylori (H. pylori) is one of the most common bacterial stomach infections and is implicated in a majority of stomach and duodenum ulcer as well as may be gastric cancer. The study showed that the incidence in diyala is nearly high comparing with the surrounding, little known about H. pylori prevalence in this population or other Native communities. In this cross-sectional study aimed to determine the prevalence of H. pylori among people subjects of different age groups ranged between 1 year to >50 years old. Two hundred and fifty of blood samples were collected from patients admitted Teaching hospitals in Baqubaa city and subjected to serological screening test.